Synthesis, Spectroscopic Study and Biological Activity of new Bidentate Schiff Base (4-(Dimethylamino) Benzylidene)-5-(3,4,5-Trimethoxybenzyl)-5 Pyrimidine-2,4-Diamine) and Transition Metal Mn(II), Ni(II) and Cu(II) Complexes - May Joda Kareem (Pakistan Journal of Medical & Health Sciences, 2022)
The Schiff bases ligand (L1) was synthesized by condensing (2,4-diamine (Trimethoxybenzyl 3,4,5)-5 pyrimidine) and (4-dimethylamino benzaldehyde). The transition metal complexes of [Mn(L1)2Cl2], [Ni(L1)2Cl2], and [Cu (L1)2Cl2] were then produced. The ligand and its metal complexes Mn(II), Ni(II), and Cu(II) were examined by analyzing the elemental composition, the metal content, the chloride content, and the molar conductance, FT-IR, 1H-NMR, UV-Vis spectra, magnetic susceptibility, mass spectra, and thermal analysis (TGA). The results indicated that the ligand behaves as a bidentate ligand in all of the complexes produced. The [Cu (L1)2Cl2] complex is more poisonous to microorganisms.